Farmer's Motives in Raising Ettawa Crossbred Goat in Yogyakarta, Indonesia - Guntoro, Budi (Medwell Journals, 2016)
Objective of this study was to determine the farmers motives in raising Ettawa crossbred goats in Yogyakarta. The method used in this study was a survey. Criteria used in sampling were farmers who joined in the animal collective housing as well as groups member that still active. The analysis used in this research was descriptive. Descriptive analysis was used to describe the characteristics of the farmers. These caharacteristics included: age, educational, farming experience, number of family members and the number of goat ownership. Motivation in raising Ettawa crossbred goat was analyzed by Likert scale, which measured respondents’ answers to each statement of questionnaire that was divided into four categories: economic, utilization of goat raised, social and motive of the utilization of resources other than goat farming. Result of the research of raising Ettawa crossbred goat motivation were that economic motives, the strongest motives that lead respondent did business of raising Ettawa crossbred goat. Another motive that affested the business of raising Ettawa crossbred goat started from the highest level was the social motives, utilization motives of resources other than goat, and utilization motives of goat owned. It also showed that farmers had a high motivation in the category of raising Ettawa crossbred goat business.